Implementasi dan pelatihan aplikasi P. O. S untuk optimalisasi pengelolaan usaha pada toko MahyaLINE casual style - Fakhira, Rajwa; Muthmainmah; Siti nurhalimah (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
This research is a community service activity that focuses on the implementation and training of Point of Sale (P.O.S) applications at Warung Bang Amat, aiming to improve business efficiency and management. This topic was chosen because many small businesses face challenges in effectively managing transactions and inventory. The methods used in this study included observations, interviews, and data analysis to evaluate the impact of implementing the P.O.S. The results showed a significant improvement in transaction efficiency, inventory management, and financial monitoring after the implementation of P.O.S. In addition, the training provided to warung owners and staff successfully improved their understanding and skills in using the application. Thus, this study provides valuable insights for small business owners to adopt modern technology to improve their business performance and management. In conclusion, the adoption of technologies such as P.O.S not only supports the success of small businesses, but also contributes to the overall development of the local economy.